Factors influencing the Implementation of Electronic Medical Records (Remics) based on Unified Theory of Acceptance and Use of Technology (UTAUT) in Sidoarjo Hospital: Faktor yang mempengaruhi Implementasi Rekam Medis Elektronik (Remics) berdasarkan Teori Unified Theory of Acceptance and Use of Technology (UTAUT) di RSUD Sidoarjo - Cholifah; Dijaya, Rohman; Gracia, Aisyah Silvia; Nisak, Umi Khoirun (Universitas Muhammadiyah Sidoarjo, 2022)
Information and Communication Technology has played an important role in improving the efficiency, quality and access to health services. Despite the unintended consequences of information technology in health care and treatment, current studies consistently prove that care and treatment in health care makes technology a necessity for improving the quality of health services. There are few studies related to the adaptation of information technology in health services. In addition to the need for an adaptation process towards electronic medical records, hospitals and other health facilities need to anticipate problems that may arise from the use of electronic medical records. If the use of electronic medical records can be utilized properly, it is expected to facilitate more efficient health services and increase patient satisfaction in health services. This research is a quantitative research conducted analytically to describe the factors that influence the Implementation of Electronic Medical Records (Remics) based on the Unified Theory of Acceptance and Use of Technology (UTAUT) at Sidoarjo Hospital. Data obtained from survey results through questionnaires. The research population is all Health Workers in Sidoarjo Hospital. The sample of this study was Health Workers of RSUD Sidoarjo which were taken randomly with a total of 20 people. The study was conducted on March 1-25, 2022. The results showed that the direct effect of EE on BI was 0.061, which means that if EE increased by one unit, BI could increase by 6%. This effect is positive. The effect of FC on BI is -0.310, which means that if FC increases by one unit, BI can decrease by 31%. This effect is negative. The effect of SI on BI is -0.549, which means that if SI increases by one unit, BI can decrease by 54%, this effect is negative. From the results and discussion above, it can be concluded that the variables that influence the intention to use Electronic Medical Records (remics) in Sidoarjo Hospital are Effort Expectancy (EE), Facilitating Condition (FC) and Social Influence (SI).